Integrasi Media Digital dalam Model Problem Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis pada Materi Gelombang Siswa Kelas VIII SMP - Salmah, Salmah (Gravity Edu : Jurnal Pembelajaran dan Pengajaran Fisika, 2025)
This study examines the effectiveness of integrating digital media into the Problem Based Learning (PBL) model to improve students’ critical thinking skills on wave concepts in Grade VIII at SMPN 8 Kota Bima. Using a quasi-experimental pretest–posttest control group design, the study involved Class VIII-A as the experimental group (32 students) and VIII-B as the control group (30 students). Instruments were developed based on Facione’s critical thinking indicators and validated through expert judgment. Results indicate a significant improvement in the experimental class, with an N-gain of 0.71 (high category), while the control class reached 0.40 (medium category). Independent t-test analysis confirmed significant differences between the two groups in posttest scores for both critical thinking skills and learning outcomes. Thus, integrating digital media within the PBL model effectively enhances students’ critical thinking and conceptual understanding of waves